2015
DOI: 10.1038/ejcn.2015.119
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of hypertension in the Polish arm of the HAPIEE cohort study

Abstract: Background/objectives Coffee consumption has been hypothesized to be associated with blood pressure, but previous findings are not homogenous. The aim of this study was to evaluate the association between coffee consumption and the risk of developing hypertension. Subjects/Methods Data on coffee consumption, blood pressure, and use of anti-hypertensive medicament were derived from 2,725 participants of the Polish arm of the HAPIEE project (Health, Alcohol and Psychosocial factors In Eastern Europe) who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 51 publications
2
48
1
1
Order By: Relevance
“…In fact, we found that hypertension was associated with a significantly lower consumption of caffeinated coffee and with a non-statistically significant higher consumption of decaffeinated coffee, which is consistent with results from other studies [25]. An inverse association between coffee consumption and hypertension has also been reported in other studies [24,26]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, we found that hypertension was associated with a significantly lower consumption of caffeinated coffee and with a non-statistically significant higher consumption of decaffeinated coffee, which is consistent with results from other studies [25]. An inverse association between coffee consumption and hypertension has also been reported in other studies [24,26]. …”
Section: Discussionsupporting
confidence: 93%
“…The association with smoking and alcohol use was stronger for caffeinated coffee consumption and weaker for decaffeinated coffee, for which the association with smoking was not significant. In accordance with previous studies, it was found that older people consumed less caffeinated coffee [24], which may be related to the higher prevalence of some chronic diseases, such as hypertension, and the clinical recommendations to decrease or even quit coffee consumption at older ages [25]. In fact, we found that hypertension was associated with a significantly lower consumption of caffeinated coffee and with a non-statistically significant higher consumption of decaffeinated coffee, which is consistent with results from other studies [25].…”
Section: Discussionsupporting
confidence: 91%
“…It might be possible that the protective effect of coffee consumption comes through a different physiology than that through reducing atherosclerosis, such as by reducing risk factors responsible for cardiovascular disease. Coffee consumption has been associated with a lower risk of diabetes type 2 [15], improvement of insulin sensitivity [16], hypertension [17], and decreased LDL-C oxidation [18], primarily due to its anti-inflammatory [19] and anti-oxidant [20] properties.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interest has been directed towards other bioactive compounds found in fruit and vegetables, namely, polyphenols (Duthie et al , ) that might mediate the benefits independent of the abundant antioxidants. Epidemiological studies have also shown that polyphenols found in berries (Ellingsen et al , ; Li et al , ), chocolate (Jumar and Schmieder, ; Larsson et al , ), coffee (Grosso et al , ) and red wine (Cosmi et al , ) are associated with slower CVD progression. However, given their low bioavailability, the assumption that the observed health beneficial effects are driven by their direct antioxidant activity (chemical antagonism) seems very unlikely.…”
Section: Antioxidant Therapies In Cvdmentioning
confidence: 99%